2010
DOI: 10.1039/c0cc00792g
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the photoinduced magnetism in copper octacyanomolybdates

Abstract: Ab initio calculations show that a possible mechanism for the photomagnetism in copper octacyanomolybdate compounds consists of the initial excitation of the diamagnetic Cu(II)-Mo(IV-CS) pair to a Cu(II)-Mo(IV-T) state, whose geometry relaxation stabilizes the magnetic doublet and quartet states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…One important example is the deactivation mechanism of DNA, which must be very rapid and efficient to make it photoresistant [6][7][8][9][10][11][12][13][14]. Another important process is the light-induced magnetism in transition metal complexes such as the prussian blue analogs [15][16][17][18], cyanomolybdates [19][20][21][22], or Fe II coordination complexes [23][24][25][26]. The theoretical study of light-induced mechanisms faces some important difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…One important example is the deactivation mechanism of DNA, which must be very rapid and efficient to make it photoresistant [6][7][8][9][10][11][12][13][14]. Another important process is the light-induced magnetism in transition metal complexes such as the prussian blue analogs [15][16][17][18], cyanomolybdates [19][20][21][22], or Fe II coordination complexes [23][24][25][26]. The theoretical study of light-induced mechanisms faces some important difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above theoretical calculations, the selective 405 nm excitation allows the lower‐energy triplet state to be reached. Complementary calculations were performed to obtain the optimized geometry of the triplet state, which shows a geometry change for Mo from octa‐ to heptacoordination, similarly to what has been computed for Cu II /Mo IV (CN) 8 systems …”
Section: Figurementioning
confidence: 95%
“…This scenario was confirmed for Co II /W V (CN) 8 systems, but for specific Cu II /Mo IV (CN) 8 systems, the results of X‐ray magnetic circular dichroism revealed a singlet–triplet crossover centered on the Mo IV . Additionally, theoretical calculations have suggested the photoinduced formation of a triplet located on Mo concomitant with the breakage of one Mo−CN bond in [Mo(CN) 8 ] 4− …”
Section: Figurementioning
confidence: 99%
“…Up to now, photomagnetic processes in Cu(II)-Mo(IV) systems have been considered in terms of two possible mechanisms: metal-to-metal charge transfer (MMCT): paramagnetic Cu II (S = 1/2)⋯Mo IV-LS (S = 0)⋯Cu II (S = 1/2) → ferromagnetic Cu I (S = 0)⋯[Mo V-LS -Cu II ](S total = 1), 27,[29][30][31]33,36,[38][39][40][41]43,44,[46][47][48][49][50][51][52][53][54][55] and a Light-Induced Excited Spin-State Trapping (LIESST) effect on the Mo(IV) centre: paramagnetic Cu II (S = 1/2) ⋯Mo IV-LS (S = 0)⋯Cu II (S = 1/2) → ferromagnetic [Cu II -Mo IV-HS -Cu II ](S total = 2). [27][28][29][31][32][33]35,37,42,45 The latter case may result from the photoinduced formation of an intermediate geometry between the ideal geometries of TDD-8 and SAPR-8 (Fig. 5) 32,35,60 or the photodissociation of the single cyanide leading to a reduction of the coordination number to 7.…”
Section: Magnetic and Photomagnetic Studiesmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24] The greatest successes in developing photomagnetic materials were achieved for octacyanidometallate based systems, 25,26 in particular for copper(II)-molybdenum(IV) ones. 27 Furthermore, it was found that Cu II -Mo IV photomagnetic assemblies can be based on polynuclear molecules, [28][29][30][31][32][33][34][35][36][37][38][39][40][41] chains, 33,[42][43][44] layers 33,[45][46][47] and three-dimensional networks 33,[48][49][50][51][52][53][54][55] with at least one bridging cyanide per single copper(II) centre. Surprisingly, ionic systems with an isolated [Mo(CN) 8 ] 4− anion were not considered, assuming that the photomagnetic phenomenon in Cu II -Mo IV compounds originates from the light-induced MMCT mechanism.…”
Section: Introductionmentioning
confidence: 99%